Exploration of the Relationship Between the Population and Football Stadiums in Romania - Grigore Vasile Herman; Tudor Caciora; Mariana Laura Herman; Mihai Șandra; Gheorghe Codruț Bulz (Urban Science)
A sport is a specific human activity with deep cultural and social meanings that involves cooperation and competitiveness according to well-established rules. One of the most representative sports at the local and global levels is football thanks to the large number of people and resources involved in supporting it. The aim of the study is to explore the connection between communities and football stadiums at a spatial level (development region, county and cities). From a methodological point of view, multicriteria analysis (eight criteria, four for the population and four for football stadiums) was utilized to determine and define the various relationships between the population and football stadiums. The obtained results highlighted, at the spatial level, the existence of some non-correlations between the population and football stadiums. Thus, the existence of strong relationships at the level of development regions (75%), followed by those established at the level of cities (24.1) and counties (2.4), were identified. The strongest relationships were established in the Northwest, Central and South development regions; in Bihor County and in cities like Bucharest, Brașov, Constanta and Iași.